2022
DOI: 10.1111/ane.13615
|View full text |Cite
|
Sign up to set email alerts
|

Sports and trauma as risk factors for Motor Neurone Disease: New Zealand case–control study

Abstract: Objectives To assess whether sports, physical trauma and emotional trauma are associated with motor neurone disease (MND) in a New Zealand case–control study (2013–2016). Methods In total, 321 MND cases and 605 population controls were interviewed collecting information on lifetime histories of playing sports, physical trauma (head injury with concussion, spine injury) and emotional trauma (14 categories). ORs were estimated using logistic regression adjusting for age, sex, ethnicity, socioeconomic status, edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
4
2
Order By: Relevance
“…Limited data suggest exposure to TBI, including sports concussion, might serve as a risk factor for MND 33–36. However, the risk observed in this study and similar athlete studies appears several-fold higher than that reported from research looking at non-sport associated TBI 36. As such, the possibility that head impacts and/or TBI in sport lead to greater risk of MND than non-sports TBI, or that an additional, unknown risk factor contributes to the remarkably high risk observed among these populations, might be considered.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Limited data suggest exposure to TBI, including sports concussion, might serve as a risk factor for MND 33–36. However, the risk observed in this study and similar athlete studies appears several-fold higher than that reported from research looking at non-sport associated TBI 36. As such, the possibility that head impacts and/or TBI in sport lead to greater risk of MND than non-sports TBI, or that an additional, unknown risk factor contributes to the remarkably high risk observed among these populations, might be considered.…”
Section: Discussioncontrasting
confidence: 75%
“…Furthermore, as we had to allocate an MND event to the comparison group, to obviate the problem of a zero count, the reported effect size is likely to be an underestimate of the true strength of association. Limited data suggest exposure to TBI, including sports concussion, might serve as a risk factor for MND 33–36. However, the risk observed in this study and similar athlete studies appears several-fold higher than that reported from research looking at non-sport associated TBI 36.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Repetitive head injuries with concussion over a period of 15 years, playing sports in general, and playing soccer in particular are a risk factor for ALS. [114][115][116] A meta-analysis of more than 37 000 male professional soccer players showed a significantly higher mortality risk from motor neuron disease. 117 In a cluster of professional soccer players, a 6,5-fold risk of developing ALS was found, compared with the general population.…”
Section: Amyotrophic Lateral Sclerosis In Soccer Playersmentioning
confidence: 99%
“…Adverse events, such as prior exposure to heavy metals (including lead), pesticides, physical trauma/injury, electric shock history, and prior exposure to organic solvents, are significantly associated with the progression of MND and serve as risk factors for MND [3]. A study of the New Zealand population revealed that cranial trauma, prolonged strenuous exercise, and emotional trauma (particularly in patients 162 with chronic mental stimulation) can cause MND to progress faster compared with the general population, which experienced none of the above [41]. Interestingly, certain psychological interventions can significantly improve the quality of life for MND patients [42,43].…”
Section: Stress Impacts the Progress Of Mndmentioning
confidence: 99%